BRAZILIAN AND SPANISH PANORAMA ON DOCTORAL DISSERTATIONS IN THE AREA OF HIGH ABILITY / GIFTEDNESS - Pedro, Ketilin Mayra [UNESP]; Moriel Chacon, Miguel Claudio [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
In Brazil the area of High Ability/Giftedness was initialy contemplated in LDB 5692/71 (BRASIL, 1971), while in Spain the starting point occurs on the Real Decreto 696/1995 (ESPANHA, 1995), ensuring to the student body the right of identification and care. Aiming to contribute with the researches in this area, we elaborated the actual brazilian and Spanish panorama regarding the doctoral theses about HA/G. To perform this investigation we consulted the Brazilian Digital Library of Theses and Dissertations and the Database of Doctoral Theses. There were found a total of 70 theses, wherein 20 brasilian and 50 spanish. Based on the analysis of the title, the abstract and the keywords, we listed thematic categories, wherein predominant: Identity, Identification, Evaluation. The first brazilian theses defended date 1989, while in Spain the first theses date 1990. Regargind the publishing place, in Brazil we realize there is a predominance over federal universities, while in Spain, the Universidade Comlutense de Madrid excels in the number of publications. We realize that although the number of publications has grown steadily, this figure is still incipiente in comparison with the number of publications of other areas and the labor demand that these studants require.
Keywords: High abilities/giftedness; Literature review; Brazil; Spain